Eficiência de paraquat no controle de azevém resistente ao glyphosate em diferentes horários de aplicação e níveis de sombreamento - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The ryegrass is a major weed in winter cereals. The continuous glyphosate herbicide use for ryegrass control selected biotypes resistant to EPSPs-inhibiting enzyme. Thus, the paraquat herbicide aids as control alternative. This herbicide has contact action acting in photosystem I. The application time can influence directly in its efficiency, because the meteorological conditions such as temperature, humidity and brightness change during the day. Therefore, the objective of this study was to evaluate the efficiency of paraquat in ryegrass control at different times of applications and shading levels. The experimental design was in bands and, randomized within each band, with trifactorial 6 x 3 x 2, with five replicates. The A factor was composed of six hours of paraquat application (3:00; 7:00; 11:00; 15:00; 19:00 and 23:00 hours of the day), the B factor was three levels of shading (control no shading; 50 and 100% brightness reduction), the factor C was two evaluation times of control ryegrass (1st evaluation time - 48 hours and 2nd evaluation time - 120 hours after treatment application).The variables evaluated were control and shoot dry matter. To control, was adopted grading in percentage scale where 0% was lack of control and 100% plant death. For shoot dry matter, the plants were cut up to the ground and taken to greenhouse until constant weight. Variance analysis was realized, when significant was used Fischer LSD test to compare means between treatments (p ≤ 0.05). There was interaction for the three factors studied. The level of 100% absence of light showed the less control and greater shoot dry matter. The application at three hours in the treatment of 0% shading showed greater control in the first and second evaluation time. The shading of 100% reduced herbicide paraquat efficiency. The most control was observed in the second evaluation time. Paraquat application at 3 hours is more efficient to control ryegrass for levels of 0 and 50% of shading. The efficiency in ryegrass control resistant to glyphosate herbicide to paraquat varies by application time and shading level. In general, the higher shading level show less efficiency ryegrass control.
Keywords: Luminosidade; Herbicida; Plantas daninhas; Luminosity; Herbicide; Weeds; CNPQ::CIENCIAS AGRARIAS